2015
DOI: 10.1007/s10509-015-2245-3
|View full text |Cite
|
Sign up to set email alerts
|

The Galactic kinematics of cataclysmic variables

Abstract: Kinematical properties of CVs were investigated according to population types and orbital periods, using the space velocities computed from recently updated systemic velocities, proper motions and parallaxes. Reliability of collected space velocity data are refined by removing 34 systems with largest space velocity errors. The 216 CVs in the refined sample were shown to have a dispersion of 53.70 ± 7.41 km s −1 corresponding to a mean kinematical age of 5.29 ± 1.35 Gyr. Population types of CVs were identified … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Ak et al (2015) derives a similar result. The donors in longer period CVs appear to have more dramatic abundances anomalies than do the short period systems.…”
mentioning
confidence: 53%
“…Ak et al (2015) derives a similar result. The donors in longer period CVs appear to have more dramatic abundances anomalies than do the short period systems.…”
mentioning
confidence: 53%
“…Regardless, the majority of the observed CVs in the field seem to be much younger than GC CVs. Ak et al (2015) inferred kinematic ages in a sample of field CVs and concluded that 94 per cent of CVs in the solar neighbourhood belong to the thin-disc component of the Galaxy. Mean kinematical ages of 3.40 ± 1.03 and 3.90 ± 1.28 Gyr were found for the non-magnetic thin-disc CVs below and above the period gap, respectively.…”
Section: Discussion On the Age-dependence Of CV Propertiesmentioning
confidence: 99%
“…For instance, Belloni et al (2016) quantified the observational selection effects that plague the search for CVs in GCs, and concluded that their detection rates could be dramatically increased if detectable during quiescence. Ak et al (2015) inferred the ages of a sample of field CVs from kinematic data, and concluded that 94 per cent of CVs in the solar neighbourhood belong to the thin-disc component of the Galaxy. The corresponding mean kinematical ages are 3.40 ± 1.03 Gyr and 3.90 ± 1.28 Gyr for the non-magnetic thin-disc CVs below and above the period gap, respectively.…”
Section: Agementioning
confidence: 99%
“…The constraints are as follows: (i) Z max ⩽ 825 pc and (ii) e p ⩽ 0.10. The first parameter was first used by Ak et al (2015), while the second appeared in Huang et al (2015), who used the range e p < 0.13 to separate the cold thin-disc stars from the thick-disc stars. The vertical distance Z max = 825 pc is the place where space densities of the thin and thick discs are compatible.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted the procedure detailed in Ak et al (2015) to separate the sample stars into different populations. Thus, stars with Z max ⩽ 825 pc are assumed to be thin-disc stars, while those with Z max > 825 pc are categorised as thick disc or perhaps halo stars.…”
Section: The Datamentioning
confidence: 99%